Afetação patrimonial: proteção ao patrimônio das pessoas com deficiência - Coura, Luísa Bueno (2021)
The present dissertation proposes to analyze and study a way to protect Persons with Disabilities discernment due to impairment, who, before the advent of the Law 13.146/2015 and its changes in the text of the 3rd and 4th articles from the Civil Code, have been considered as unable. Being aware that the reform which has been intended by the Statute for the Impaired Person has been noble and entailed good results, it is not proper, however, not to highlight the vulnerability, and specifically the patrimonial one takes us an interest, to which those people are exposed. The presented suggestion covers the patrimonial affectation, to the example of the patrimonial destination act of the Italian right, provided in the 2645-ter article from Civil Code from that country, since, therefore, it would remain the heritage as being protected and the impaired person would consist as aided, which would allow, once she is able to exercise her autonomy with regard to the existential acts, the heritage remaining as ensured.